Environmental Knowledge, Awareness, Attitude Toward Purchase Intervention Intervened by Infrastructure Readiness and Price Affordability of Electric Vehicle (Ev): Case in Indonesia - Ramadhan, Naufalian; Nurdayadi; Alfiandri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This research aims to identify factors that influence Electric Vehicles (EV) ownership in Indonesia, including environmental knowledge, awareness, attitudes and affordability as intervention factors in purchasing decisions. Method: A quantitative approach was used with a questionnaire survey of 136 eligible respondents. Research Findings: Environmental knowledge, awareness, and attitudes have a positive influence on ownership of Electric Vehicles (EV). Attitudes also have a significant impact on purchase intentions, with price affordability as an intervening factor. Theoretical Contribution: This research adds to the literature on the adoption of environmentally friendly technology and consumer behavior in owning Electric Vehicles (EV) in Indonesia. Implications for Practitioners: The research results provide insights for manufacturers, marketers, and policymakers to increase the adoption of Electric Vehicles (EV) through education, environmental awareness campaigns, and price incentives. Research Limitations: Limitations of this research include the limited sample size and not considering infrastructure and policy factors that can also influence the adoption of Electric Vehicles (EV).